Energy Conservation in Buildings with Passive Heating & Cooling Strategies: A Prospective Study in Greece’s Climatic Zones - Sofia Giannarou; Michael Tsatiris (Current Approaches in Science and Technology Research Vol. 7, 2021)
This study aims to guide engineers and architects in the implementation of passive heating and cooling strategies, in order to ensure thermal comfort to building users at the lowest possible cost. Proposed passive heating and cooling strategies are also presented. Buildings are a significant energy consumer with a high potential for energy savings.Building energy efficiency can be significantly improved with the use of appropriate technical and cost-effective technologies, with corresponding environmental and social benefits. The application of bioclimatic design techniques is particularly important in terms of a building’s energy performance. This word refers to a design that, while taking into account the local environment, aims to provide the best indoor comfort conditions while minimising energy use and utilising available natural resources. Passive heating and cooling systems are systems that use natural sources (sun, wind, etc.) to heat or cool a building without the use of mechanical means. The purpose of passive system design is to improve thermal comfort while saving energy for as long as possible. With the use of passive heating and cooling systems, this study investigates the possibilities of delivering thermal comfort conditions in regions of Greece with different climatic circumstances. The Olgyay bioclimatic charts, which are designed for temperate regions, are used to conduct the bioclimatic analysis. The findings show how passive design strategies affect occupant thermal comfort and provide architects and engineers with design guidelines for energy-independent buildings.